KEMAMPUAN PEMECAHAN MASALAH SISWA DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN GAYA BELAJAR PADA MATERI PECAHAN DI SMP - Winarti, Desi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aim to describe the problem solving ability of students in solve of fraction story problem in term of their learning style. The research method used descriptive method with case study. The subject in this research were eight students 7th grade of SMP Negeri 7 Pontianak that are 2 students who have diverger learning style, 2 students who have assimilator learning style, 2 students who have converger learning style, and 2 students who have accomodator learning style. The result of the data analysis showed that the problem solving ability of students in solve of fraction story problem are different depending on their learning style. The problem solving ability of students in solve of fraction story problem who haveÂ  assimilator learning style able satisfy all the indicators of problem solving that are understanding the problem, devising a plan, carrying out the plan, and looking back. Student who have converger learning style able satisfy all the indicator of problem solving, but there is one student who is less able satisfy part Â indicators of problem solving, students who have diverger learning style only able satisfy some indicat ors of problem solving, and students who have accomodator learning style able satisfy two indicators of understanding the problem, while other indicators are less satisfy even not fulfilled. Keyword: Problem Solving Ability, Story Problem, Learning Style